2010
DOI: 10.1287/mnsc.1100.1225
|View full text |Cite
|
Sign up to set email alerts
|

Reference Dependence in Multilocation Newsvendor Models: A Structural Analysis

Abstract: W e propose a behavioral theory to predict actual ordering behavior in multilocation inventory systems. The theory rests on a well-known stylized fact of human behavior: people's preferences are reference dependent. We incorporate reference dependence into the newsvendor framework by assuming that there are psychological costs of leftovers and stockouts. We also hypothesize that the psychological aversion to leftovers is greater than the disutility for stockouts. We then experimentally test the proposed theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
252
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(277 citation statements)
references
References 32 publications
23
252
1
1
Order By: Relevance
“…By doing so, we avoid experimental results to be influenced by the "pull-to-center" effect when setting the inventory quantity; the phenomenon of systematically ordering too little when the cost of underage is high and ordering too much when the cost of overage is high. This phenomenon may be explained by some well-known decision biases, e.g., anchoring and insufficient adjustment, observation bias, reference-dependent preferences and is well documented in the literature in single newsvendor [5,7,47] and multilocation newsvendor models [28]. The number of participants in each treatment was decided based on the supply chain group synthesis in each case (one vs. two retailers), taking into account the probability that a specific group will play more than once and the average number of rounds a given group is expected to play.…”
Section: Experiments 451 Experimental Design and Proceduresmentioning
confidence: 94%
See 1 more Smart Citation
“…By doing so, we avoid experimental results to be influenced by the "pull-to-center" effect when setting the inventory quantity; the phenomenon of systematically ordering too little when the cost of underage is high and ordering too much when the cost of overage is high. This phenomenon may be explained by some well-known decision biases, e.g., anchoring and insufficient adjustment, observation bias, reference-dependent preferences and is well documented in the literature in single newsvendor [5,7,47] and multilocation newsvendor models [28]. The number of participants in each treatment was decided based on the supply chain group synthesis in each case (one vs. two retailers), taking into account the probability that a specific group will play more than once and the average number of rounds a given group is expected to play.…”
Section: Experiments 451 Experimental Design and Proceduresmentioning
confidence: 94%
“…They find that the value of pooling may be negative when the inventory policy in use is suboptimal while it varies little across the distributions they studied. More recently, [28] study experimentally the ordering behavior in multilocation inventory systems and they show that systematic biases eliminate the risk-pooling benefit when the demand across stores is strongly correlated. They propose a behavioral theory based on reference dependence (psychological aversion to leftovers is greater than the disutility of stockouts) to explain / predict ordering behavior in a multi-location newsvendor framework, under both a centralized and a decentralized inventory structure.…”
Section: Behavioral Issues In Inventory Pooling Decisionsmentioning
confidence: 99%
“…For example, Schweitzer and Cachon (2000) first found the pullto-center effect in the newsvendor problem. Various influencing factors in newsvendor decisions are also investigated, such as decision heuristics (Bostian et al 2008), the role of learning and feedback Katok 2008, Lurie andSwaminathan 2009), demand estimation biases (Feiler et al 2012), psychological costs (Ho et al 2010), and bounded rationality (Su 2008, Kremer et al 2010. In a serial supply chain setting, Sterman (1989) and Donohue (2005, 2006) found that human subjects do not sufficiently account for the pipeline inventory and subsequently overreact to their inventory levels, contributing to the bullwhip effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other promising applications include the optimal contract form and compensation schemes for loss-averse chief executive officers (de Meza and Webb 2007, Dittmann et al 2010, and Herweg et al 2010; consumption insensitivity to bad news of future income (Bowman, Minehart, and Rabin 1999); optimal ordering when managers or news vendors are loss averse (Ho et al 2010, Wang and Webster 2007, and Wang 2010; and so on.…”
Section: Prospect Theorymentioning
confidence: 99%